Job-fit its drivers and outcomes among HR practitioners. [article]. - Lanuza, Godofredo A.
This study examined job-fit, its driver and outcomes among 131 human resources(HR)practitioners in the Philippines. The study showed Filipino HR practitioners are strong in HR functional competencies and process skills such as communication and group facilitation. However, they also report significant gaps in strategic thinking, change management, and organization diagnosis. Job-fit is related to education attainment, job level,and tenure. Job-fit is likewise correlated with career satisfaction and commitment. Areas of HR practice that practitioners wish to pursue more are organization and career development. On the other hand, the results show a relative lack of interest in employee relations and recruitment and selection.